Diseño óptimo de la composición de un detergente líquido para la ropa teniendo en cuenta las preferencias del mercado (2017)
"In this project, it is presented a methodology for the optimal product design of a liquid laundry detergent. The optimal product design is a new field of study in chemical engineering with the desire of reducing costs and developing time, considering these are the key factors for liquid laundry detergents in a competitive market. To estimate the liquid detergent properties, needed in the design there were used mathematical models found in literature. There properties were used later in consumer preferences functions to assign a preference value to de liquid detergent that depends on the likeness of the consumer towards the properties. This value is then used on a competitive market model, estimating the price and demand of the product to calculate the profit in the market." -- Tomado del Formato de Documento de Grado.